2014
DOI: 10.1371/journal.pgen.1004345
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Pathway-Based Approach Identifies Association between Genomic Regions at CTCF and CACNB2 and Schizophrenia

Abstract: In the present study, an integrated hierarchical approach was applied to: (1) identify pathways associated with susceptibility to schizophrenia; (2) detect genes that may be potentially affected in these pathways since they contain an associated polymorphism; and (3) annotate the functional consequences of such single-nucleotide polymorphisms (SNPs) in the affected genes or their regulatory regions. The Global Test was applied to detect schizophrenia-associated pathways using discovery and replication datasets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 60 publications
3
38
0
Order By: Relevance
“…Several studies have provided support to the hypothesis by showing increased brain Bax/Bcl-2 ratios and decreased levels of Bcl-2 and GSK3 [114116]. In addition, a comprehensive integrated pathway analysis of GWAS and gene expression data also pointed to aberrant apoptosis as a potential cause of SZ [110]. In our study, we found similar evidence.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have provided support to the hypothesis by showing increased brain Bax/Bcl-2 ratios and decreased levels of Bcl-2 and GSK3 [114116]. In addition, a comprehensive integrated pathway analysis of GWAS and gene expression data also pointed to aberrant apoptosis as a potential cause of SZ [110]. In our study, we found similar evidence.…”
Section: Discussionsupporting
confidence: 89%
“…Findings from the current study point to converging evidence from pathway-based studies that identified similar biological mechanisms including axon guidance (91-93), cell adhesion (94, 95), inflammation and immune system (96) associated with SZ risk. A recent BSNIP resting fMRI-genetic study (32) using Para-ICA identified similar processes including developmental neurogenesis, axon guidance, synaptic and cadherin cell adhesion, immune response, nervous system development, ceramide and sphingosine pathways mediating aberrant default mode activity in psychosis.…”
Section: G9supporting
confidence: 56%
“…These findings point to a potential mechanism of action underlying meQTL function and molecular consequences. In support of a role in SCZ, CTCF has been recently identified in an integrated pathway approach for pathways and genes affected in SCZ [75]. Together, these findings suggest a regulatory role for fetal meQTLs and highlight with CTCF an important mechanism connecting genomic variation to genomic function.…”
Section: Meqtls In Sczmentioning
confidence: 84%